Still our most important asset: A systematic review on human resource management in the midst of the Fourth Industrial Rrevolution - Salvatore Ammirato; Alberto Michele Felicetti; Roberto Linzalone; Vincenzo Corvello; Satish Kumar (Journal of Innovation & Knowledge (JIK), 2023)
The digital transition is transforming society in general and industry in particular, so much so that the concept of Industry 4.0 is by now widespread and consolidated. However, there is the risk that too pronounced a focus on technology may lead to losing sight of the centrality of human resources. Among others, the European Commission has urged greater attention from research and industry on the human factor. There is a need for further theorizing concerning the role of humans in a digitalized industry. Understanding what is known in the literature on human resource management in an Industry 4.0 context is an important first step toward defining a roadmap for enhancing the human factor in a digitized industry. To achieve this goal, we conducted a systematic analysis of the literature. We used a text-mining approach implemented via the MySLR software platform, which uses latent Dirichlet allocation, to analyze 566 papers published in academic journals. In this way, we were able to identify the main trends in the literature, the most frequently analyzed topics, and the gaps and possible future developments. Our study provides a synthesis of the research in this domain, as well as a research framework based on three pillars related to the technological, human-centric, and organizational perspectives. The results provide researchers and managers with a clear and updated overview of research in the field of human resource management in the context of Industry 4.0, as well as future research directions.
Keywords: O14; O15; 650; Human capital; Human Resource Management; Industry 4.0; MySLR; Systematic literature review